2022
DOI: 10.1096/fj.202200434rr
|View full text |Cite
|
Sign up to set email alerts
|

TNF‐α‐dependent lung inflammation upregulates PD‐L1 in monocyte‐derived macrophages to contribute to lung tumorigenesis

Abstract: Chronic inflammation, which is dominated by macrophage-involved inflammatory responses, is an instigator of cancer initiation. Macrophages are the most abundant immune cells in healthy lungs, and associated with lung tumor development and promotion. PD-L1 is a negative molecule in macrophages and correlated with an immunosuppressive function in tumor environment. Macrophages expressing PD-L1, rather than tumor cells, exhibits a critical role in tumor growth and progression. However, whether and how PD-L1 in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 55 publications
(160 reference statements)
0
7
0
Order By: Relevance
“…There is a signi cant overlap between CD68 and CSN6, and these dates showed CSN6 expression in macrophage in model of sepsis. Wen et al showed that suggested TNF-α upregulated CSN6 expression in lung in ammation [20]. These data showed that CSN6 is involved in the progression of sepsis disease or sepsis-induced myocardial injury.…”
Section: Discussionmentioning
confidence: 91%
“…There is a signi cant overlap between CD68 and CSN6, and these dates showed CSN6 expression in macrophage in model of sepsis. Wen et al showed that suggested TNF-α upregulated CSN6 expression in lung in ammation [20]. These data showed that CSN6 is involved in the progression of sepsis disease or sepsis-induced myocardial injury.…”
Section: Discussionmentioning
confidence: 91%
“…Chemokine receptor‐like 2 (CCRL2) can bind with chemokine‐like receptor 1 (CMKLR1) and promote the recruitment of CMKLR1‐expressing immune cells, such as monocytes, DC, and NK cells 28 . The protein expression of CMKLR1 in lung tissues was elevated in a rat model of PAH 29,30 . Cd274, also known as programmed cell death‐ligand 1 (PD‐L1), can bind with programmed death protein‐1 (PD‐1) to inhibit lymphocyte activation and proliferation 31 .…”
Section: Resultsmentioning
confidence: 99%
“… 28 The protein expression of CMKLR1 in lung tissues was elevated in a rat model of PAH. 29 , 30 Cd274, also known as programmed cell death‐ligand 1 (PD‐L1), can bind with programmed death protein‐1 (PD‐1) to inhibit lymphocyte activation and proliferation. 31 A previous study has found that PD‐1 and PD‐L1 proteins were overexpressed on both T and B cells in idiopathic PAH patients, which is similar with our findings.…”
Section: Resultsmentioning
confidence: 99%
“…For one thing, TNF- α can inhibit tumors via activating programmed death cascades in targeted cells, with devastating effects on the function of lysosomal enzymes and/or lysosomal membrane integrity. TNF- α signaling can also be used to induce B7-H1 and PD-L1 expression on CD8 + T cells via several pathways, thereby causing immune resistance [ 25 27 ]. We found that three different doses of aconite all increased TNF- α levels in the serum of tumor-bearing mice.…”
Section: Discussionmentioning
confidence: 99%